Perfil neuropsicológico del trastorno por estrés postraumático agudo en una muestra de personas, víctimas de un atentado con carro-bomba en Colombia : estudio descriptivo (2016)
ABSTRACT: the aim of the present study is to describe the cognitive performance on group of people whom have lived trough situations involving traumas associated with car bombings at their work facilities. Material and Methods: descriptive and correlational study that included a sample of 50 patients divided in two groups: one made up of 25 participants that were affected by traumatic experience associated with car bombing. In the other group of 25, participants that worked in the same facility; but have not had, any type of traumatic events. The groups were assimilated in various demographic variables; sex, age, socioeconomic, marital, and academic status. The tests were applied and evaluated cognitive domains of attention, memory and executive functioning. Results: omparison between both groups shows differences in the executive function tests, which may be related to alterations in the functioning of the frontal lobe. Conclusion: it is to discuss the need to take into account both the different statistics and the clinical relevance of the results, and offering the suggestion to include an assessment and intervention of the victims with post-traumatic stress variables of Neuropsychological aspects that can affect, reintegration and academic processes.